Gravitação quântica em laços : modelo de Chern-Simons e gravitação em 2+1 dimensões - Barbosa, Rodrigo Martins de Siqueira (2011)
The theory of Loop Quantum Gravity gives us an very interesting framework to handle the quantization of general gauge theories. On a work by Witten, 1989, it is proposed that General Relativity on 2+1 dimensions could be described as a gauge theory of a Chern-Simons action over a Poincar´e gauge group. The purpose of this work then is to make a possible quantum description of gravitation on 2+1 dimensions by the Chern-Simons model, and make a discussion about the observables of this model